Phytostimulants in sustainable agriculture - Bano, Asghari; Waqar, Aqsa; Khan, Asadullah; Tariq, Haleema (Frontiers in Sustainable Food Systems, 2022)
The consistent use of synthetic fertilizers and chemicals in traditional agriculture has not only compromised the fragile agroecosystems but has also adversely affected human, aquatic, and terrestrial life. The use of phytostimulants is an alternative eco-friendly approach that eliminates ecosystem disruption while maintaining agricultural productivity. Phytostimulants include living entities and materials, such as microorganisms and nanomaterials, which when applied to plants or to the rhizosphere, stimulate plant growth and induce tolerance to plants against biotic and abiotic stresses. In this review, we focus on plant growth-promoting rhizobacteria (PGPR), beneficial fungi, such as arbuscular mycorrhizal fungi (AMF) and plant growth-promoting fungi (PGPF), actinomycetes, cyanobacteria, azolla, and lichens, and their potential benefits in the crop improvement, and mitigation of abiotic and biotic stresses either alone or in combination. PGPR, AMF, and PGPF are plant beneficial microbes that can release phytohormones, such as indole acetic acid (IAA), gibberellic acid (GA), and cytokinins, promoting plant growth and improving soil health, and in addition, they also produce many secondary metabolites, antibiotics, and antioxidant compounds and help to combat biotic and abiotic stresses. Their ability to act as phytostimulator and a supplement of inorganic fertilizers is considered promising in practicing sustainable agriculture and organic farming. Glomalin is a proteinaceous product, produced by AMF, involved in soil aggregation and elevation of soil water holding capacity under stressed and unstressed conditions. The negative effects of continuous cropping can be mitigated by AMF biofertilization. The synergistic effects of PGPR and PGPF may be more effective. The mechanisms of control exercised by PGPF either direct or indirect to suppress plant diseases viz. by competing for space and nutrients, mycoparasitism, antibiosis, mycovirus-mediated cross-protection, and induced systemic resistance (ISR) have been discussed. The emerging role of cyanobacterial metabolites and the implication of nanofertilizers have been highlighted in sustainable agriculture.